Pengaruh Profesionalisme dan Locus of Control Terhadap Kinerja Badan Pengawas Lembaga Perkreditan Desa Se-Kabupaten Badung - Ida Ayu Arini Satya Dewi; Kadek Dewi Padnyawati; Ni Made Wisni Arie Pramuki (UNHI Press, 2023)
This study aims to examine the influence of professionalism and locus of control on the performance of village credit institution supervisory boards (LPD) throughout Badung Regency. The population in this study were 366 respondents who in this case were the supervisory bodies of the LPD in Badung Regency. The sampling method used was probability sampling, by determining the number of samples using the slovin formula so that 191 respondents were obtained, then to determine the number of samples in each district using a proportionate startified random sampling technique. Data analysis techniques in this study using SEM-PLS. The results of the study show that the performance of supervisory bodies in LPDs in Badung District is influenced by locus of control. Where the higher the locus of control owned by a regulatory agency, the higher its performance. Another finding in this study is that professionalism has a positive but not significant effect on the performance of supervisory bodies, this is suspected because they have not fully honed their knowledge and abilities in carrying out their duties so that it will lead to low performance of the resulting supervisory bodies